2015
DOI: 10.1002/elan.201500508
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric Determination of Sulfide by Glassy Carbon Electrode Modified with Hemin Functionalized Reduced Graphene Oxide

Abstract: This work describes a new approach for rapid detection of sulfide using a glassy carbon electrode (GCE) modified with hemin functionalized reduced graphene oxide (hemin‐rGO). The modified GCE was applied to the selective amperometric detection of sulfide at a working potential of 0.05 V (vs. Ag/AgCl) at pH 7.5, which gave a linear range of 0.002–0.212 mM, a sensitivity of 246.5 µA mM−1 cm−2, and a detection limit of 1.3 µM. The proposed method was applied in determination of sulfide‐spiked water, and the metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…A new approach for the rapid detection of sulfide was reported by Xiaodong et al. via GCE modified with hemin‐functionalized reduced graphene oxide (GCE/hemin‐rGO) [77] . The fabricated GCE/hemin‐rGO was successfully employed for the selective amperometric determination of sulfide at a working potential of +0.05 V (vs Ag/AgCl) based on the reaction between sulfide and the active site of Fe 3+ in hemin.…”
Section: Sulfide Sensing Strategies In Controlled Potential Techniquesmentioning
confidence: 99%
“…A new approach for the rapid detection of sulfide was reported by Xiaodong et al. via GCE modified with hemin‐functionalized reduced graphene oxide (GCE/hemin‐rGO) [77] . The fabricated GCE/hemin‐rGO was successfully employed for the selective amperometric determination of sulfide at a working potential of +0.05 V (vs Ag/AgCl) based on the reaction between sulfide and the active site of Fe 3+ in hemin.…”
Section: Sulfide Sensing Strategies In Controlled Potential Techniquesmentioning
confidence: 99%
“…Sulfur (S 2-), the reduced form of sulfur compounds (such as HSand H 2 S), is generally formed in waste water by anaerobic bacteria on organic matter [1]. It has been reported that over 50 ppm of sulfide concentration was declared as to be high toxicity which is harmful to the human health [2]. Beside toxic effects, the studies in the last decade approved that H 2 S acts a significant role in extending of the postharvest shelf life of many herbal foods such as vegetables and fruits [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that over 50 ppm of sulfide concentration was declared as to be high toxicity which is harmful to the human health [2]. Beside toxic effects, the studies in the last decade approved that H 2 S acts a significant role in extending of the postharvest shelf life of many herbal foods such as vegetables and fruits [2,3,4]. Also, sulfide salts have been commonly used to control the toxic metal levels in environment, because most of metal sulfides are insoluble and they are easily found as precipitated in waste waters [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene (GR), a 2D nanomaterial with single layer sp 2 hybridized carbon atoms, has been widely applied to modify electrode for its large surface area, excellent electrical conductivity, low cost, outstanding mobility charge carriers, and fast electron transfer rate. 21,22 The graphene modified electrode shows great promise for the analysis of many kinds of material such as folic acid, 23 baicalein, 24 dopamine, 25 hydrogen peroxide, 26 and environmental samples 27 etc. Compared to the uncontinuous graphene oxide, reduced graphene oxide on the GCE surface has better electron transfer ability.…”
Section: Introduction *mentioning
confidence: 99%